No effects of siblings and twin testosterone transfer on autistic traits - Melanie M. deWit; Sander Begeer; Michel G. Nivard; Elsje vanBergen (Wiley, 2022)
Abstract Background Having twin and non‐twin siblings might influence autistic traits both prenatally and postnatally. The twin testosterone transfer hypothesis suggests that girls with a twin brother are exposed to higher levels of prenatal testosterone than girls with a twin sister, and that increased testosterone exposure masculinizes neural development and increases autistic traits. Postnatally, siblings may provide example behaviour, which could reduce autistic traits. Methods We studied pre‐ and postnatal influences of twin and non‐twin siblings on mother and teacher‐reported autistic traits in 7714 dizygotic twins. We examined the effect of sex of the proband child and of the siblings. We fitted regression models (for boys and girls separately) with sex of co‐twin and having older and/or younger siblings of each sex as predictors. Results Girls' mother‐reported autistic traits were slightly lower for those with a twin brother than those with a twin sister (β = −.08, p = .001, Cohen's d = −.13). This difference was not replicated in teacher‐reported autistic traits (β = .01, p = .734). Boys' (mother and teacher‐reported) autistic traits were not related to the sex of their co‐twin (ps > 0.50). Teacher‐reported autistic traits were slightly higher if girls had an older brother (β = .07, p = .013, Cohen's d = .12). Other than this small effect, we found no effect of non‐twin siblings on autistic traits in either girls or boys (ps > .18). Conclusions We did not find increased autistic traits in girls with a twin brother compared to girls with a twin sister. This finding contributes to a body of literature that rejects the twin testosterone transfer hypothesis. In addition, we found little evidence for pre‐ and postnatal sibling influences. Our findings align with high heritability and absence of shared‐environmental influences in ASD.